Interplay between the environment and the immune system - Universidad Peruana Cayetano Heredia (2025)
About IMMUNOPERU 2025: This IUIS-ALACI-PSI course has brought together a diverse group of students, immunologists and experts to share their distinct perspectives, skills and expertise. The focus was on a variety of endemic and emerging diseases related to environmental and climate change. The goal was to catalyze the development of novel concepts, methods and approaches in addressing these emerging challenges. MAIN TOPICS: The course has addressed the Impact of environmental exposures on immunity in infectious disease, chronic inflammation and cancer with particular attention to: Changes in microbial communities and their metabolites that drive inflammatory disease (eg. effects of antibiotics, dietary and other factors) Environmental cues and pollutants linked to the development of hematologic malignancies. The impact of climate change on endemic infectious diseases (eg. Tuberculosis, Dengue Fever, Chagas Disease, and others). ABSTRACTS: 1. Decoding the Language of Tumor–Immune Communication: The Role of Extracellular Vesicles in Melanoma 2. The effect of lead (Pb) on the immune response and working memory of children and adults from Huautla, Morelos 3. Role of Bcl-3 and senescence in Colorectal Cancer 4. Assessing Cytotoxic mediators secreted by Immune Cells in Patients with Drug-Sensitive Active Pulmonary Tuberculosis Undergoing Treatment 5. Assessing Cytotoxic mediators secreted by Immune Cells in Patients with Drug-Sensitive Active Pulmonary Tuberculosis Undergoing Treatment 6. Risk assessment in the hematological and biochemical profile of patients suspected or confirmed with Zika, Dengue or Chikungunya in Valencia, Venezuela 7. Cellular exhaustion in T cell subsets and IgG (anti-Spike) antibody response in people vaccinated against the SARS-CoV-2 Virus 8. Characterization of B Cell Populations in Malaria Caused by Plasmodium vivax Using Single- Cell RNA Sequencing (scRNA-seq) 9. Seropositivity of four Serological Tests for Strongyloides spp. Detection in a Retrospective Cohort in community of the Peruvian Amazon 10. C- reactive protein levels in paraguayan patients infected with Chikungunya virus 11. Pediatric STAT3 Hyper-IgE Syndrome: A case series 12. Activated PI3K Delta Syndrome in a Pediatric Patient: A Case Report on Diagnosis and Management 13. Temporal study of inflammation and its relation to the progression of axonal damage in an animal model of neurocysticercosis 14. Deciphering the environmental impact on the leukemic niche: a redox imbalance upon acute exposure to heavy metals 15. Use of polyclonal Antibodies for the detection of circulating Trypanosoma cruzi antigens in clinical Samples 16. Airway administration of OM-85 bacterial lysate mitigates Pseudomonas aeruginosa susceptibility but aggravates inflammation and tissue damage in a preclinical cystic fibrosis model. 17. Temporal Analysis of Axonal Mitochondrial Transport Disruption in a Murine Model of Neurocysticercosis” 18. Stromal factor-driven modulation of dendritic cell activation in the melanoma tumor microenvironment 19. Biofilm Formation as a Factor Associated with Antimicrobial Resistance in Clinical Isolates of Pseudomonas aeruginosa 20. Environmental Exposure and Bone Marrow Immune Microenvironment in Pediatric Acute Leukemia in Mexico 21. Perfil sérico mineral en vacas Holstein en etapa de transición y su relación con las enfermedades de la producción, Chiclayo 2021 22. COMPARISON OF THE TUBERCULIN SKIN TEST AND QUANTIFERON-TB GOLD FOR DETECTING LATENT TUBERCULOSIS INFECTION IN POPULATIONS EXPOSED TO ENVIRONMENTAL FACTORS IN THE PERUVIAN AMAZON 23. Comparative Evaluation of Active and Latent Tuberculosis Detection Using the GeneXpert System and the QuantiFERON Test: Implications for Diagnosis and Clinical Management in Endemic Settings 24. PRELBAC: Evaluation of the Efficacy and Safety of Bacterial Lysate OM-85 in Preventing Recurrent Respiratory Infections in Children Treated at the Guillermo Almenara Irigoyen National Hospital, Lima. A Retrospective Cohort Study (2019–2023) 25. Environmental exposome and immune infiltrates in Glioblastoma: A preliminary study linking heavy metal exposure to tumor immunity in Peruvian patients 26. Neutrophil/lymphocyte ratio associated with mortality in patients with stage 5 chronic kidney disease starting hemodialysis in a public hospital. 27. Does Involving Parents in Soil Sampling Identify Causes of Child Exposure to Lead? A Case Study of Community Engagement in Mining-Impacted Towns in Peru 28. Activin A cooperates with the Actin-binding Protein Cortactin to Promote B-cell Acute Lymphoblastic Leukemia Progression 29. Molecular Characterization of CTX-M Group Genes in Clinical Escherichia coli Strains Isolated from Pediatric Patients at a Referral Hospital in Lima 30. Role of small extracellular vesicles induced by Helicobacter pylori in the promotion of in vitro angiogenesis 31. Genetic Patterns of Immune-Evasive and Carbapenem-Resistant Pseudomonas aeruginosa in a Clinical Environment 32. Particulate matter impairs immune system function by upregulating inflammatory pathways and decreasing the pathogen response, which impact SARS-CoV-2 pathogenesis 33. Antibiotic resistance genes in aquatic environments in Iquitos: impact on public and environmental health 34. Multivalent vaccine candidate from conserved immunogenic peptides in entry or exit proteins of Orthopoxvirus genus 35. Impact of Active Pulmonary TB Treatment on the Diversity of Circulating NK cells 36. Menin as therapeutic target for multiple myeloma 37. Association between segmented filamentous bacteria (SFB) colonization and the use of antibiotics in the gut immune response of TNFR1-/- mice 38. Factors associated with the transmission of congenital Chagas disease in the Hospital de la Mujer Dr. Percy Boland. 39. Association between Chagas disease in pregnant women and premature births in a public hospital in Santa Cruz, Bolivia 40. Unusual case of de novo psoriasis in the setting of leukocyte adhesion deficiency post hematopoietic stem cell transplantation: A case report. 41. Production of two recombinant proteins from Helicobacter pylory : CagA and HopQ as antigenic targets for a serological test prototype 42. In Silico Screening of Molecules Targeting TIP60-FOXP3 Interaction Inhibition as a Strategy to Block Treg Cell Modulation in the Tumor Microenvironment 43. Ivermectin impairs the microbicidal capacity of macrophages in vitro by binding to the TLR- 4/MD2 complex, but is beneficial in acute pneumonia in TLR-4 knockout mice. 44. Early - onset multiple sclerosis: a case report